2022
DOI: 10.1093/ijpp/riac006
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ knowledge, attitudes and concerns regarding the disposal of expired/unused medication

Abstract: Objectives Unused/expired medicines that are improperly disposed of can enter soil and water supply and have negative implications for public health. This study aimed to assess patients’ knowledge and understanding of medication disposal practices and their willingness to participate in a medication takeback programme. Methods A self-administered questionnaire comprising of 26 questions based on demographics, knowledge, belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Amongst Nigerian community pharmacists, 16.2% used workplace garbage or pouring down the sink as their means of expired drug disposal. This was lower than that observed in Trinidad, 11 although the sample size was smaller in Nigeria. In Saudi Arabia, 16 75.3% returned expired medication to their pharmaceutical distributors whereas in Kuwait, 14 73% of pharmacists disposed of medication by pouring it down the sink/flushing in the toilet.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Amongst Nigerian community pharmacists, 16.2% used workplace garbage or pouring down the sink as their means of expired drug disposal. This was lower than that observed in Trinidad, 11 although the sample size was smaller in Nigeria. In Saudi Arabia, 16 75.3% returned expired medication to their pharmaceutical distributors whereas in Kuwait, 14 73% of pharmacists disposed of medication by pouring it down the sink/flushing in the toilet.…”
Section: Discussioncontrasting
confidence: 67%
“…for proper disposal of pharmaceutical waste. Previous work in Trinidad 11 showed that patients disposed of unused/expired medication by throwing it in the household trash. As drug experts, pharmacists must be well equipped to inform the general population on the best ways to dispose of unused/expired medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Gidey et al (2020), it was reported that improper disposal of pharmaceuticals might be harmful to the environment and 77.4% disposed of pharmaceuticals by throwing them in household garbage [ 20 ]. In another study on medication disposal, it was reported that participants mostly disposed of medicines by throwing them in household garbage [ 21 ]. The dominant view was that unused pharmaceuticals were generally accumulated in households, expired pharmaceuticals were thrown in household garbage, pharmaceuticals were stored in the kitchen, and improper disposal harmed the environment in literature.…”
Section: Discussionmentioning
confidence: 99%